M2 A randomised, double-blind, placebo-controlled trial evaluating cysteamine in huntington's disease. (13th September 2016) - Bonneau, Dominique; Bachoud-Lévi, Anne-Catherine; Durr, Alexandra; Goizet, Cyril; Azulay, Jean-Philippe; Simonin, Clémence; Tranchant, Christine; Calvas, Fabienne; Krystkowiak, Pierre; Olivier, Audrey; Saudou, Frédéric; Maison, Patrick; et al.
Abstract : Background: Cysteamine has been demonstrated as potentially neuroprotective in numerous animal models of Huntington's disease (HD). Methods: Ninety-six early-stage HD patients were randomised to a double-blind trial to receive 600 mg delayed-release cysteamine bitartrate (DR-CB) (51) or placebo (45) twice a day for 18 months. The primary endpoint was the change from baseline in the Unified Huntington's Disease Rating Scale (UHDRS) Total Motor Score (TMS) at 18 months. Key secondary endpoints included other UHDRS scales: total functional capacity, independence, cognition and behaviour. Results are expressed as the least-squares mean (LSM) treatment-effect difference of DR-CB minus placebo; negative values indicating less deterioration relative to placebo. Results: The mean baseline TMS (± SD) was 24.2 (10.7) (5 to 53 points). The 18 month treatment-effect (LSM ± standard error [± SE]) was not statistically significant: −1.5 (1.71) points (95% CI: −4.9; 1.9; p = 0.385); representing less mean (± SE) increase (deterioration) from baseline in DR-CB- compared with placebo-treated patients: 4.9 (1.17) versus 6.4 (1.25) points, respectively. No significant treatment-effects were observed for key secondary endpoints. DR-CB was safe and well-tolerated. Post-hoc analyses dichotomized by median baseline TMS (<23/≥23 points) indicated a statistically significant DR-CB treatment-effect (± SE): −4.7 (2.18) points (p = 0.038) in patients with baseline TMS ≥ 23 points. Interpretation: Statistical significance was not observed for the primary endpoint. However, post-hoc analysis indicated statistical significance in patients with more severe baseline motor impairment. Further studies involving a larger number of patients are warranted. Trial registration: EudraCT Number: 2010–019444-39